Wash and Nutrition outcomes in Children. - Dangour, Alan D. (Tufts University. Tisch Library., 2016)
Sanitation plays a significant role in nutrition and particularly, reducing stunting. This presentation draws links, discusses enviornmental enteropathy, and suggests interventions. Delievered on Day 1 of the 2014 Scientific Symposium in Kathmandu Nepal.; Nutrition School: NIL Symposium Presentations, 2014.; Keywords: WASH.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy